Impact of COVID-19 on intrapartum care at public hospitals in the Sidama region, Ethiopia: A mixed-methods study - Zemenu Yohannes Kassa; Vanessa Scarf; Sabera Turkmani; Deborah Fox (Women's Health)
Background: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the health of pregnant women and their unborn babies. Objective: To explore the impact of COVID-19 on intrapartum care in Ethiopia. Design: A concurrent mixed-methods design was employed. Methods: An interrupted time series analysis was implemented using a Poisson regression model to estimate monthly changes in the incidence rates of institutional childbirth, instrumental vaginal birth, caesarean section, stillbirth, institutional neonatal death, institutional maternal death and availability of essential medical supplies before and during COVID-19. The dataset included data from all women who gave birth in 15 public hospitals, and the total number of childbirths in the cohort study before COVID-19 (12 months of data from March 2019 to February 2020) was 24,478, while during COVID-19 (6 months of data from March to August 2020), the total number of childbirths in the cohort study was 11,966, forming a combined final dataset of 36,444. Simultaneously, a descriptive qualitative study using a purposive sampling technique was conducted through in-depth interviews until data saturation was reached, with data were collected from 14 February to 10 May 2022. Data from the interviews were imported into NVivo 12 Plus to perform an inductive thematic analysis. Quantitative and qualitative data were integrated using joint display methods to identify corroboration or contradiction between the different forms of evidence. Results: Our findings indicate that the incidence rates of caesarean sections and instrumental vaginal births significantly increased in the first 6 months of COVID-19. Three themes were identified: ‘ Barriers to providing intrapartum care during COVID-19 ’, ‘ Delays to provision of intrapartum care during COVID-19 ’ and ‘ Inadequate COVID-19 preventive measures ’. Conclusion: In combination, the three themes contributed to a considerable increase in neonatal and maternal deaths. Interventions such as fully equipped labour wards and obstetric triage systems are needed to restore disrupted maternal and perinatal care during the ongoing and future pandemics. In addition, stakeholders should inform the public that blood donations can help the community recover from recent shocks in emergency health and future pandemics. Further research should investigate the long-term impact of COVID-19 on maternity care and maternal and infant outcomes.